2013
DOI: 10.1016/j.toxlet.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a gap-junctional intercellular communication (GJIC) assay using cigarette smoke

Abstract: Inhibition of gap-junctional intercellular communication (GJIC) via exposure to various toxic substances has been implicated in tumor promotion. In the present study, cigarette smoke total particulate matter (TPM), a known inhibitor of GJIC, were used to characterize a new GJIC screening assay in three independent experiments. The main features of this assay were automated fluorescence microscopy combined with non-invasive parachute technique. Rat liver epithelial cells (WB-F344) were stained with the fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The obtained EC 50 values for TPA in studied cell lines were comparable to range of the values published in previous studies 51,67 . Similarly, GJIC-inhibitory activities of fluoranthene and 18-β-glycyrrhetinic acid in WB-F344 cells evaluated by our innovative assay were similar with previously reported studies 26,52,68 . By screening GJIC stimulators, we confirmed that our multiparametric assay can be also used for assessment of chemopreventive agents, such as caffeic acid phenethyl ester 69 or sodium butyrate 70 , which were previously found to restore cell-cell communication in neoplastically transformed, GJIC-deficient WB-F344-ras cells.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The obtained EC 50 values for TPA in studied cell lines were comparable to range of the values published in previous studies 51,67 . Similarly, GJIC-inhibitory activities of fluoranthene and 18-β-glycyrrhetinic acid in WB-F344 cells evaluated by our innovative assay were similar with previously reported studies 26,52,68 . By screening GJIC stimulators, we confirmed that our multiparametric assay can be also used for assessment of chemopreventive agents, such as caffeic acid phenethyl ester 69 or sodium butyrate 70 , which were previously found to restore cell-cell communication in neoplastically transformed, GJIC-deficient WB-F344-ras cells.…”
Section: Discussionsupporting
confidence: 90%
“…As summarized in the Supplementary Table S3, some of these methods for GJIC assessment have been recently adapted for HTS and/or HCA/HCS. These assays are mostly based on commonly used dye-transfer techniques such as electroporation 21 , laser perforation 22 , microinjection 23 , microfluidic loading 24,25 , parachute/preloading assay [26][27][28] , or on a luminometric or fluorimetric sensing of specific molecules exchanged via gap junctions between donor and recipient cells 29,30 . However, these methods can require a special equipment (electroporating 21 , microscopic 22,27,28 , microinjecting 23 , microfludic 24,25 ), that is not commonly available in a laboratory, and proprietary, closed source software for high-throughput image analysis 21,22,26,28 , or rely on specialized transduced cell models 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations